Diversity of Sea Cucumber Types in Shallow Sea Waters of Katapang Sukarame Carita Labuan Pandeglang Banten Beach - Fikri Nurhidayatulloh; Usman Setiawan; Nurullah Asep Abdilah; Suyamto Suyamto (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Cucumbers of the sea are one of the animals from the phylum Echinodermata that have ecological and economic roles. Biogeographically, the types of sea cucumbers from the Holothuriidae family are not yet well known in the waters of Shallow Waters of Katapang Sukarame Carita Labuan Pandeglang Banten Coast, particularly the information on the types and their phylogenetic relationships. This study aims to determine the diversity and phenetic relationship between types of sea cucumbers in Shallow Waters of Katapang Sukarame Carita Labuan Pandeglang Banten Coast. The research has stages which include preliminary observations of sea cucumber species. Preliminary observations were carried out by surveying the location of the sea cucumber catch and interviewing local fishermen. The results of the survey on preliminary observations were used as the basis for determining the sampling station. Sampling of the specimens was carried out using a cruising technique based on a predetermined sequence of sampling stations. Observations and species determination were carried out to obtain data as material for the analysis of taxonomy and phenetic relationships. The research results show that the diversity of sea cucumber species found in the Shallow Waters of Katapang Sukarame Carita Labuan Pandeglang Banten Coast are S. horrens, H. atra, and H. leucospilota. There is a phylogenetic relationship among the three sea cucumber species in the Shallow Waters of Katapang Sukarame Carita Labuan Pandeglang Banten Coast. Group 1, which consists of H. atra, has a similarity of 85.393% with H. leucospilota. Group 2, which includes S. horrens, has a similarity of 64.130% with H. atra and H. leucospilota.